Circulation of nutrients through bio-based fertilizer products: perspectives from farmers, suppliers, and civil society - Kvakkestad, Valborg; Brod, Eva; Flø, Bjørn E.; Hanserud, Ola; Helgesen, Hilde (Frontiers in Sustainable Food Systems, 2023)
Closing nutrient cycles by bio-based fertilizer products (BFPs) can improve the environmental sustainability of food systems and facilitate a more circular economy. Although the theoretical potential for nutrient recycling has been explored in detail, BFPs still seldom replace mineral fertilizer products in practice. The aim of the present study was to explore the critical enabling and limiting factors for the use of BFPs as seen from the perspective of farmers, suppliers, and civil society. To this aim, qualitative interviews were conducted with seven conventional grain farmers, six suppliers of BFPs, and five representatives of civil society, limited to environmental non-governmental organizations. The presented results illustrate a mismatch between demand and supply. On the one hand, the interviewed farmers were only interested in using BFPs if they are practical to use, balanced with respect to nutrient contents, and potentially provide the same earnings as mineral fertilizers. Positive effects for soil quality were an important driver for many of the farmers. On the other hand, the suppliers of BFPs were generally not able to offer products that fulfilled the farmers’ demands without economic losses, and they emphasized that they have faced several regulatory challenges. Representatives of regional civil society organizations expressed concern that new technical solutions could cause new environmental challenges, and that BFPs could enable further intensification of livestock production. The central-level representatives from the same NGOs, however, were positive about that BFPs can solve environmental problems. Policy instruments will be needed to increase the adoption of PFPs. Fostering BFPs’ that contribute to a sustainable agriculture is important to consider when formulating these polices.